Experimental investigation of the relation between H− negative ion density and Lyman-α emission intensity in a microwave discharge. (3rd February 2016) - Aleiferis, S; Tarvainen, O; Svarnas, P; Bacal, M; Béchu, S
Abstract: A new mechanism for producing negative ions in low density and low power hydrogen plasmas was proposed recently. It refers to anion formation due to collisions between hydrogen atoms being in the first excited state. The proposed mechanism was indirectly supported by the quadratic relation observed between the extracted negative ion current and Lyman- α radiation of a filament-driven arc discharge, when borrowed data from the literature were combined. The present work provides experimental data comparing directly the absolute negative ion density and Lyman- α radiation in an ECR-driven hydrogen plasma source. The previously mentioned quadratic relation is not observed in the specific source studied, underlying the difficulty of distinguishing between the proposed mechanism and other negative ion production paths.